Design of Solar-Powered Cold Storage with Thermoelectric Cooling to Improve Fruit Storage Quality: A Case Study of Local Fruit Sellers - Hendra; Leni, Desmarita; Mulyadi; Zinvi Fu; Sir Anderson (Universitas Negeri Padang, 2024)
The main problem faced by local farmers and fruit vendors is the lack of efficient and energy-saving storage facilities, causing fruits to often experience quality degradation and spoilage. This study aims to design and test a prototype of solar-powered cold storage with a thermoelectric cooling system (TEC) as an energy-efficient and environmentally friendly storage solution. The prototype uses a 100-watt solar panel as the primary energy source, combined with a Peltier TEC1 module to generate cooling. The test results show that the system can lower the internal temperature to 12°C within 3 hours. The system also achieves an energy efficiency of 18.07%, which is considered sufficient for small-scale thermoelectric applications. The use of solar energy enables the system to operate independently without relying on conventional electricity, offering an energy-saving and environmentally friendly solution. This prototype is deemed suitable for application in tropical regions, such as Indonesia, which has abundant solar energy potential throughout the year. This technology is expected to be a practical solution for farmers and small-scale vendors to reduce post-harvest losses while supporting carbon emission reduction efforts in the agricultural sector.